CHALLENGES FOR UNIVERSITIES TO ONLINE TECHNOLOGIES IMPLEMENTATION IN THE CONDITIONS OF WAR IN UKRAINE - Yuliia Sytnykova; Tаtyana Petrenko; Oksana Bezkorovaina; Anastasiia Ptushka (Інформаційні технології і засоби навчання)
The experience of online education in Ukraine during wartime is unique. After the Russian-Ukrainian war beginning, in a month of so-called "holidays", in spring 2022, from April, 1, by the order of the Ministry of Education and Science of Ukraine and the rectors' orders of universities, online education started. The classes were online, and it was difficult to overcome the war stress, but the experience of the pandemic taught everyone to work with online technologies such as Zoom, Meet, and Google Classroom. Teaching students online was carried out as online as offline with the university platforms like Moodle and others for offline learning, they contained all educational materials from the previous two years of the pandemic, tasks, quizzes, and tests. The purpose of the research is to identify pedagogical, psychological, and technical challenges for teaching university students during the war in Ukraine with the survey method. The survey was conducted online with 65 university lecturers and 122 students from 5 universities in Kharkiv, Ukraine. The pedagogical, psychological, and technical difficulties were analyzed. The questions were aimed at studying such aspects as 1) pedagogical and psychological difficulties: the teachers/students' readiness for online teaching/learning, 2) pedagogical difficulties: the procedures of online teaching/learning and technologies, in particular, methods, forms, means of giving/mastering knowledge, 3) psychological and technical difficulties faced both by teachers and students. The results are as follows. The acquired teaching and learning experience with online technologies helped to establish online education in wartime positively in general. The main pedagogical difficulties were overcome with basic methods (online and offline), teaching forms such as lectures, seminars, and practical classes online, and offline, and, finally, different tools/means/platforms (video/audio recordings, corresponding emails, social networks, Moodle platform, etc.). The psychological state of both teachers and students in the circumstances of online education was also examined. The most common psychological difficulties with online learning were connected with external ones as constant shelling, and air alarms as with internal ones as stress, anxiety, worries, depression, burnout, sadness, and frustration. The technical difficulties were connected to blackouts, lack of Internet connection, power outages, evacuation, changes in living and working conditions, relocations, and the impossibility of using laboratory equipment. The conclusion is despite all online difficulties, the quality of teaching did not change significantly, thanks to the clear understanding that it is a necessity to teach and learn online.